The Influence of Perception of Customer Bonding on Customer Loyalty of Naavagreen Products in Madiun City - Tri Lestariningsih; Triana Prihatinta; Srimiatun; Clarista Bunga Ramadhani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of customer bonding perceptions on customer loyalty for Naavagreen products in Madiun City. The population in this research were all consumers of beauty products at the Naavagreen Clinic, Madiun City. The research sample is some consumers of beauty products at the Naavagreen Clinic, Madiun City, totaling 100 people. Data obtained by using a questionnaire. The sampling technique in this research uses probability sampling and simple random sampling. Hypothesis testing using multiple linear regression analysis with the help of SPSS 22. The results of hypothesis testing indicate that Perception of Customer Bonding has a positive effect on Customer Loyalty at Naavagreen Madiun Beauty Clinic.